PERAN CONSUMER ATTITUDE SEBAGAI VARIABEL MEDIASI ANTARA HEALTH CONSCIOUSNESS DAN BRAND IMAGE TERHADAP PURCHASE ITENTION PRODUK PURE MATCHA DI KALANGAN GENERASI Y DAN Z - Esti Maulida Apriliana; Laily Muzdalifah (JURNAL LENTERA BISNIS, 2026)
The focus of this study is to examine the influence of health consciousness and brand image on purchase intention, with consumer attitude acting as a mediating variable, regarding pure matcha products among Generation Y and Z. The background to this study relates to the increasing demand for pure matcha driven by health consciousness among Generation Y and Z. A survey was conducted among 140 respondents from Generation Y and Z using a quantitative research approach. The data were analysed using Structural Equation Modelling (SEM) supported by SmartPLS software. The results of the study indicate that Health Consciousness and Brand Image have a positive and significant influence on Consumer Attitude. Furthermore, Brand Image and Consumer Attitude were found to have a positive and significant influence on Purchase Intention, whilst Health Consciousness did not have a significant direct influence on Purchase Intention. Further findings indicate that Consumer Attitude mediates the influence of Brand Image on Purchase Intention. This research suggests that building a strong brand image and managing consumer attitudes are key components in enhancing the intention to purchase pure matcha products particularly among Generation Y and Z